COUNTERING THE CRIMINAL INCOME LEGALIZATION GAINED BY ELECTRONIC MONEY - Natalia Kunitsyna; Ekaterina Dyudikova (Вестник Северо-Кавказского федерального университета)
The authors predict the dynamics of quantity and amount of the transactions made by electronic money in the Russian Federation in the medium term; allocated the conditions allowing to use electronic money in doubtful transactions and the illegal purposes; considered the signs specifying a possibility to involve the electronic money in criminal legalization or terrorism financing; offered recommendations about enhancement of the actions directed to counteraction to money laundering gained in the criminal way in the sphere of electronic money.